PENGARUH ISLAMIC CORPORATE SOCIAL RESPONSIBILITY (ICSR) TERHADAP REPUTASI PERUSAHAAN - Nur wahyu (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2019)
Sharia commercial banks are tasked with collecting and distributing public funds. Sharia commercial banks must be trustworthy and improve company performance by providing value to the community and the corporate environment. The better the Islamic Corporate Social Responsibility (ICSR), the better the value and reputation of the company according to shareholders, the public and bank customers. The study aims to examine the effect of Islamic Corporate Social Responsibility on the reputation of sharia commercial banks registered at the OJK in the period 2014-2017. Research uses quantitative approaches and annual reports obtained from the OJK website. ICSR variables are measured by the SRI index and reputation variable of the company is measured by the value of market share. The analysis method uses panel data regression analysis. The results of study, ICSR has a significant effect on the company's reputation. The conclusion is ICSR in accordance with the legitimacy theory that companies that express social responsibility will influence the business continuity and reputation of the company.